2009
DOI: 10.1016/j.ijpsycho.2009.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia and effort mobilization in dysphoria: Reduced cardiovascular response to reward and punishment

Abstract: Instigated by evidence for reduced responsiveness to reward in depression, the present two studies addressed the question if such anhedonic behavior would also become evident in reduced mobilization of mental effort in terms of cardiovascular reactivity. Undergraduates completed the Center for Epidemiologic Studies-Depression Scale (CES-D) and worked on mental tasks, expecting either no consequence, a performance-contingent reward, or a performance-contingent punishment. Study 1 revealed that participants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 48 publications
7
48
0
Order By: Relevance
“…All positive, negative, and overall mood scores were correlated with the depression score, r(54)s [ :43 j j, ps \ .001. These correlations replicate previous findings when the CES-D scale was administered in the end, rather than at the beginning of the experimental session (see Brinkmann et al 2009). …”
Section: Cardiovascular Baselinessupporting
confidence: 88%
See 1 more Smart Citation
“…All positive, negative, and overall mood scores were correlated with the depression score, r(54)s [ :43 j j, ps \ .001. These correlations replicate previous findings when the CES-D scale was administered in the end, rather than at the beginning of the experimental session (see Brinkmann et al 2009). …”
Section: Cardiovascular Baselinessupporting
confidence: 88%
“…Therefore, we also assessed and analyzed PEP reactivity by means of the same impedance cardiograph and in the same way as described, for instance, by Brinkmann et al (2009). Due to a software upgrade the sampling rate was 1,000 Hz without down-sampling-contrary to previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, depressed individuals report less anticipated pleasure (e.g., Chentsova-Dutton and Hanley, 2010), show impaired reward-learning behavior (e.g., Huys et al, 2013;Liu et al, 2011;Vrieze et al, 2013), demonstrate impaired reward-related decision making (e.g., Kunisato et al, 2012;Treadway et al, 2012), have reduced activity in approach-related cortical regions (e.g., Shankman et al, 2013; for a review see Thibodeau et al, 2006), and show altered activity in reward-related brain regions (for a review see Zhang et al, 2013). Recently, we have shown reduced effort-related cardiovascular reactivity during goal pursuit in subclinical depression (Brinkmann and Franzen, 2013;Brinkmann et al, 2009;Brinkmann, 2015, 2016a). …”
Section: Reward Responsiveness In Depressionmentioning
confidence: 89%
“…In other words, the higher the reward at stake, the more important is success and, therefore, the higher is the effort people mobilize (Richter, 2012; for a more detailed discussion of motivational intensity theory and its predictions see Richter, 2013;Richter et al, 2016). Using tasks with unclear difficulty, several studies have demonstrated that clinically and subclinically depressed individuals show weaker cardiovascular responses during the execution of cognitive tasks, which are instrumental to obtain a monetary reward (Brinkmann and Franzen, 2013;Brinkmann et al, 2009;Brinkmann, 2015, 2016b;Franzen et al, 2016). At least two processes are possibly involved in causing reduced effort-related cardiovascular reactivity by depressed individuals in this situation.…”
Section: Effort Mobilization and Cardiovascular Responsementioning
confidence: 99%
“…These studies used effort-related cardiovascular reactivity as the operationalization of anticipatory reward and punishment responsiveness (Brinkmann & Franzen, 2013;Brinkmann, Franzen, Rossier, & Gendolla, 2014;Brinkmann, Schüpbach, Ancel Joye, & Gendolla, 2009;Franzen & Brinkmann, 2015). Results demonstrate that subclinical depression (i.e., dysphoria) is linked to reduced effort mobilization during incentive anticipation compared to the effort nondysphoric individuals mobilize.…”
Section: Reward and Punishment Anticipation From An Effort Mobilizatimentioning
confidence: 99%